2018
DOI: 10.1097/sap.0000000000001646
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Sciatic Nerve Histology and Electrical Function After Compression and After Neurolysis in a Diabetic Rat Model

Abstract: Background Diabetic rats are more sensitive to nerve entrapment. This study was conducted to evaluate nerve function and histological changes in diabetic rats after nerve compression and subsequent decompression. Methods A total of 35 Wistar rats were included. The experimental group was divided into diabetic sciatic nerve compression group (DSNC, n = 5) and diabetic sciatic nerve decompression group (DSND, n = 20). The DSNC model was created by wrappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Double staining of the nerve demonstrated partial remyelination of axons on day 28, which was compatible with the recovery of muscle mass (Figure 2). Similar findings were reported by Hu et al, demonstrating that axon remyelination was observed 6 weeks after nerve decompression in chronic sciatic nerve compression [22].…”
Section: Discussionsupporting
confidence: 90%
“…Double staining of the nerve demonstrated partial remyelination of axons on day 28, which was compatible with the recovery of muscle mass (Figure 2). Similar findings were reported by Hu et al, demonstrating that axon remyelination was observed 6 weeks after nerve decompression in chronic sciatic nerve compression [22].…”
Section: Discussionsupporting
confidence: 90%
“…Since that review, further evidence has been published/addressing delayed mortality, prolonged survival without recurring ulceration, and improved intra‐operative evoked motor potentials 6,9 . Animal models of induced diabetes with evolving sciatic nerve trunk enlargement and compression demonstrate progressive behavioural, myelination and electrophysiologic changes, but recovery to nearly normal status by 3 months following ND 10 . This animal modelling closely mimics the course and pathologic findings of human DPN.…”
mentioning
confidence: 77%
“…6,9 Animal models of induced diabetes with evolving sci- but recovery to nearly normal status by 3 months following ND. 10 This animal modelling closely mimics the course and pathologic findings of human DPN.…”
mentioning
confidence: 83%
“…26 It is known that accompanying diabetes as a concomitant disease in these patients will cause the nerve to be more sensitive due to compression-related edema. 27 In our study, nearly half of the patients in each group were diagnosed with regulated diabetes mellitus.…”
Section: Discussionmentioning
confidence: 67%